Financial Reporting Practices and Internal Corporate Governance Mechanisms in Emerging Markets - Rajpurohit, Punita Dhansingh; Rijwani, Parag Rajkumar (Prabandhan: Indian Journal of Management, 2020)
Empirical research based on principal – agent conflicts has revealed that corporate governance plays an important role in governing financial reporting practices in developed markets. The emerging markets, however, are characterized by principal – principal conflict. The institutional specificities of emerging markets are significantly different from those in developed markets, and thus, their corporate governance mechanisms and financial reporting practices are also different. This study aimed at critically reviewing 50 most relevant studies focusing on emerging markets to study the role of corporate governance in governing financial reporting practices. The articles were analyzed based on the proxies for measuring financial reporting and corporate governance, sample, methodology, and major findings. The review revealed that earnings quality is the most widely used proxy of financial reporting and majority of the articles examined two or more corporate governance mechanisms together. The synthesis of the findings revealed that different corporate governance mechanisms impact earnings quality and disclosure quality differently.